FEATURES OF QUANTITATIVE ESTIMATION OF FLAVONOID CONTENT IN JUGLANS NIGRA L. BARKS PREPARATIONS - V. A. Kurkin; N. I. Zimenkina (Фармация и фармакология (Пятигорск))
The aim of the research is the development of quantification procedures of flavonoids in Juglans nigra L. barks preparations using modern instrumental analytical techniques (spectrophotometry, high performance liquid chromatography).Materials and methods. The subjects of research were tincture and dry extract of Juglans nigra L. bark, the samples of which were prepared in March and April 2020 in the Botanical Garden of Samara State Medical University (Samara); the standard samples (SS) of myricitrin, myricetin. The registration of the electronic spectra was carried out with a spectrophotometer «Specord 40» (Analytik Jena, Germany). The chromatographic analysis was carried out by the method of reversed-phase HPLC on a microcolumn liquid chromatograph “Milichrom-6” (NPAO “Nauchpribor”, Russia).Results. Using differential spectrophotometry, methods for the quantitative determination of the total amount of flavonoids in terms of myricitrin in the tincture and dry extract of Juglans nigra L. bark, has been developed. It has been determined that the content of the total amount of flavonoids in terms of myricitrin in the tincture and dry extract of Juglans nigra L., is 0.84±0.07% and 12.38±0.24%, respectively. The error of a single determination of the total amount of flavonoids in terms of myricitrin in the tincture and dry extract of Juglans nigra L. bark with a confidence probability of 95%, is ± 8.91% and ± 2.10%, respectively. Methods for the quantitative determination of myricitrin in the tincture and dry extract of Juglans nigra L. bark by HPLC has been developed. The content of the dominant flavonoid – myricitrin (myricetin-3-O-α-L-rhamnopyranoside) – in the tincture and dry extract of Juglans nigra L., was 0.42±0.06% and 8.45±0.24%, respectively. The error of the single determination of myricitrin in the tincture and dry extract of Juglans nigra L. with a confidence probability of 95% is ± 15.04% and ±2.96%, respectively.Conclusion. The developed methods for the quantitative determination of flavonoids in the preparations of Juglans nigra L. barks L. can be used in solving the problems of standardization of Juglans nigra L. preparations.